Tracking the complex flow of chromosome rearrangements from the Hominoidea Ancestor to extant Hylobates and Nomascus Gibbons by high-resolution synteny mapping - Misceo, Doriana; Capozzi, Oronzo; Roberto, Roberta; Dell’Oglio, Maria P.; Rocchi, Mariano; Stanyon, Roscoe; Archidiacono, Nicoletta

(untitled) (Genome Research, 2008)
In this study we characterized the extension, reciprocal arrangement, and orientation of syntenic chromosomal segments in the lar gibbon (Hylobates lar, HLA) by hybridization of a panel of ∼1000 human BAC clones. Each lar gibbon rearrangement was defined by a splitting BAC clone or by two overlapping clones flanking the breakpoint. A reconstruction of the synteny arrangement of the last common ancestor of all living lesser apes was made by combining these data with previous results in Nomascus leucogenys, Hoolock hoolock, and Symphalangus syndactylus. The definition of the ancestral synteny organization facilitated tracking the cascade of chromosomal changes from the Hominoidea ancestor to the present day karyotype of Hylobates and Nomascus. Each chromosomal rearrangement could be placed within an approximate phylogenetic and temporal framework. We identified 12 lar-specific rearrangements and five previously undescribed rearrangements that occurred in the Hylobatidae ancestor. The majority of the chromosomal differences between lar gibbons and humans are due to rearrangements that occurred in the Hylobatidae ancestor (38 events), consistent with the hypothesis that the genus Hylobates is the most recently evolved lesser ape genus. The rates of rearrangements in gibbons are 10 to 20 times higher than the mammalian default rate. Segmental duplication may be a driving force in gibbon chromosome evolution, because a consistent number of rearrangements involves pericentromeric regions (10 events) and centromere inactivation (seven events). Both phenomena can be reasonably supposed to have strongly contributed to the euchromatic dispersal of segmental duplications typical of pericentromeric regions. This hypothesis can be more fully tested when the sequence of this gibbon species becomes available. The detailed synteny map provided here will, in turn, substantially facilitate sequence assembly efforts.